Spectrum of NSD1 mutations in Sotos and Weaver syndromes. Issue 6 (1st June 2003) - Rio, M; Clech, L; Amiel, J; Faivre, L; Lyonnet, S; Le Merrer, M; Odent, S; Lacombe, D; Edery, P; Brauner, R; Raoul, O; Gosset, P; et al.
Abstract : Sotos syndrome is an overgrowth syndrome characterised by pre- and postnatal overgrowth, macrocephaly, advanced bone age, and typical facial features. Weaver syndrome is a closely related condition characterised by a distinctive craniofacial appearance, advanced carpal maturation, widened distal long bones, and camptodactyly. Haploinsufficiency of the NSD1 gene has recently been reported as the major cause of Sotos syndrome while point mutations accounted for a minority of cases. We looked for NSD1 deletions or mutations in 39 patients with childhood overgrowth. The series included typical Sotos patients (23/39), Sotos-like patients (lacking one major criteria, 10/39), and Weaver patients (6/39). We identified NSD1 deletions (6/33) and intragenic mutations (16/33) in Sotos syndrome patients. We also identified NSD1 intragenic mutations in 3/6 Weaver patients. We conclude therefore that NSD1 mutations account for most cases of Sotos syndrome and a significant number of Weaver syndrome cases in our series. Interestingly, mental retardation was consistently more severe in patients with NSD1 deletions. Macrocephaly and facial gestalt but not overgrowth and advanced bone age were consistently observed in Sotos syndrome patients. We suggest therefore considering macrocephaly and facial gestalt as mandatory criteria for the diagnosis of Sotos syndrome and overgrowth and advanced bone age as minor criteria.